EL PERAL PSYCHIATRIC HOSPITAL ARCHIVE: A RESEARCH EXPERIENCE FROM THE CULTURAL HISTORY OF PSYCHIATRY - Araya Ibacache, Claudia; Morales Sáez, Nicolas; Leyton Robinson, César (Revista de Historia Social y de las Mentalidades, 2024)
This article reports on a documentary research work at the El Peral Psychiatric Hospital in Santiago de Chile with the aim of reflecting on its particularities related to both its content and access to information. This means analyzing both the challenges involved in working with clinical histories, photographs and historical documents related to the medical therapies implemented and the material and cultural difficulties in accessing archives that have been historically closed to the community.
Keywords: Psychiatric Records; Health Institutions; Isolation; Asylums